A convenient and safe method to generate a large quantity of Aspergillus parasiticus spores - D. Brown; J. Salvo (Fungal Genetics Reports, 1992)
In order to examine the spore pigments in strains of Aspergillus parasiticus, we developed a method to safely generate a large quantity of spores while conserving laboratory space, resources, and time.